Inflation hardship, gender, and mental health - Patricia Louie; Cary Wu; Faraz V. Shahidi; Arjumand Siddiqi (Elsevier, 2023)
Inflation hit a 40 year high in the United States in 2022, yet the impact of inflation related hardships on distress is poorly understood, particularly the impact on women, whose income is already more limited. Using data from the US Household Pulse Survey (September-November 2022), we test whether exposure to inflation hardships is associated with greater distress and whether this association is moderated by gender (n = 119,531). We draw on a list of eighteen inflation related hardships (e.g., purchasing less food, working additional jobs, delaying medical treatment) to construct an ordinal measure of exposure to inflation hardship ranging from "no inflation hardship" to "five or more inflation hardships." We observe that an increasing number of inflation hardships is associated with higher levels of distress. We find no evidence of gender differences in the magnitude of that association at lower levels of inflation hardship (four inflation hardships or less). However, our findings suggest that exposure to five or more inflation hardships is more strongly associated with distress among men compared to women. The current study provides new insights into the cumulative burden of inflation hardships on mental health and the role that gender plays in this association.